THE EFFECTIVENESS OF STORY COMPLETION TOWARD STUDENTS’ SPEAKING ABILITY - Ida Yulianawati (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2019)
Speaking is an activity used by the people to communicate with others. According to Zhang (2009), speaking remains the most difficult skill to master for the majority of English learners, and they are still incompetent in communicating orally in English”. Many people are difficult to speak English. This research aims to find out the effectiveness of story completion effective toward students’ speaking skill. To solve the problem above, the writer would like to apply the story completion technique in teaching speaking from Kayi (2006). Quasi-experimental was applied as the method of the research. The research was conducted in SMA N Krangkeng with 66 participants; 34 students from X MIPA 1 as the control group and 32 students from X MIPA 2 as the experimental group. To collect the data, a speaking test was given to the participants. Based on the statistical analysis the technique of story completion was successfully improved the students’ speaking ability.